Zinc finger BED-type containing 3 promotes hepatic steatosis by interacting with polypyrimidine tract-binding protein 1 - Wu, Yao; Yang, Min; Wu, Shao-bo; Luo, Pei-qi; Zhang, Cheng; Ruan, Chang-shun; Cui, Wei; Zhao, Qiu-rong; Chen, Lin-xin; Meng, Juan-juan; Song, Qiang; Zhang, Wen-jin; et al. (Diabetologia, 2024)
Aims/hypothesis The relationship between metabolic dysfunction-associated steatotic liver disease (MASLD) and type 2 diabetes mellitus, insulin resistance and the metabolic syndrome is well established. While zinc finger BED-type containing 3 (ZBED3) has been linked to type 2 diabetes mellitus and the metabolic syndrome, its role in MASLD remains unclear. In this study, we aimed to investigate the function of ZBED3 in the context of MASLD. Methods Expression levels of ZBED3 were assessed in individuals with MASLD, as well as in cellular and animal models of MASLD. In vitro and in vivo analyses were conducted using a cellular model of MASLD induced by NEFA and an animal model of MASLD induced by a high-fat diet (HFD), respectively, to investigate the role of ZBED3 in MASLD. ZBED3 expression was increased by lentiviral infection or tail-vein injection of adeno-associated virus. RNA-seq and bioinformatics analysis were employed to examine the pathways through which ZBED3 modulates lipid accumulation. Findings from these next-generation transcriptome sequencing studies indicated that ZBED3 controls SREBP1c (also known as SREBF1 ; a gene involved in fatty acid de novo synthesis); thus, co-immunoprecipitation and LC-MS/MS were utilised to investigate the molecular mechanisms by which ZBED3 regulates the sterol regulatory element binding protein 1c (SREBP1c). Results In this study, we found that ZBED3 was significantly upregulated in the liver of individuals with MASLD and in MASLD animal models. ZBED3 overexpression promoted NEFA-induced triglyceride accumulation in hepatocytes in vitro. Furthermore, the hepatocyte-specific overexpression of Zbed3 promoted hepatic steatosis. Conversely, the hepatocyte-specific knockout of Zbed3 resulted in resistance of HFD-induced hepatic steatosis. Mechanistically, ZBED3 interacts directly with polypyrimidine tract-binding protein 1 (PTBP1) and affects its binding to the SREBP1c mRNA precursor to regulate SREBP1c mRNA stability and alternative splicing. Conclusions/interpretation This study indicates that ZBED3 promotes hepatic steatosis and serves as a critical regulator of the progression of MASLD. Data availability RNA-seq data have been deposited in the NCBI Gene Expression Omnibus ( www.ncbi.nlm.nih.gov/geo/query/acc.cgi?acc=GSE231875 ). MS proteomics data have been deposited to the ProteomeXchange Consortium via the iProX partner repository ( https://proteomecentral.proteomexchange.org/cgi/GetDataset?ID=PXD041743 ). Graphical Abstract